PENGARUH CAFE ATMOSPHERE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA POS SHOP COFFEE TOFFEE SIMPANG - WULANSARI, ESTI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The food service businesses began to look at coffee shop business. Coffee shop owners must have strong competitiveness in order to survive. A coffee shop should be able to create a cozy cafe atmosphere with a concept that is unique and different from the other coffee shop. That is because in order for consumers to interested and comfortable when they are in the coffee shop. Bervarian and competitive prices also influence purchasing decisions coffee shop so that they can compete with other coffee shop. From this it can be concluded that the cafe atmosphere and the price can influence consumer purchasing decisions Cafe atmosphere (X1) and price (X2) on the Post Shop Coffee Toffee Intersection of F obtained by 75.100 and 3.779 tcount for cafe atmosphere; 2.502 for the price; 2.791 with a significance level of less than 0.05, we conclude the influence simultaneously and partially between the cafe atmosphere and price on purchase decisions in Simpang Pos ToffeeCoffeeShop. Keywords: Cafe atmosphere, price